Applied periodization: a methodological approach - Naclerio, F.; Moody, J.; Chapman, M. (Journal of Human Sport & Exercise, 2013)
Periodization represents an optimal modality for organizing training programs in athletes, recreational and rehabilitative practitioners. The selected procedure, however, should be based on the athlete`s age, level of performance, specific goals or competition characteristics. A common theme throughout all periodization paradigms is the requirement to manipulate the entire program variables (intensity, volume, frequency, recovery periods and exercise selection) in order to progress from general to a more sport-specific training, dissipate fatigue and reduce the risk of injury. Although further scientific evidences are required, the understanding of periodization methodology including the appropriate procedure for designing sessions, microcycles and mesocycles is of paramount importance.